The Effectiveness of Problem Based Learning Model in Learning Reading Skills/ فعالية نموذج التعلم القائم على المشكلات في مهارة القراءة - Nurhuda, Nurhuda (Jurnal Bahasa Arab, 2025)
This research is based on several problems found at the research location, including the lack of interest in learning TPQ students in learning Arabic, students still having difficulty pronouncing sentences correctly and understanding the meaning of texts in Arabic, and the ineffective use of the learning model used. These problems result in students becoming easily bored and unable to understand Arabic reading rules. This research aims to (1) describe the application of the Problem-Based Learning model in learning reading skills at TPQ Nurul Huda Dinoyo and (2) to determine the effectiveness of using the Problem-Based Learning model in improving the reading skills ability of TPQ Nurul Huda Dinoyo students. This research uses an experimental-based quantitative approach with a quasi-experimental design and a non-equivalent control group design type. The variables used are independent variables and dependent variables. The data collection techniques used were observation, tests, and questionnaires. The data analysis used was the Shapiro-Wilk normality test, the descriptive analysis homogeneity test, and the Paired Sample T-Test hypothesis test. The results of this study are: (1) the application of the Problem-Based Learning model in learning reading skills is overall good and effective to be used as a learning model in learning reading skills because it can increase the activeness, interest in learning, and learning outcomes of students compared to the conventional learning model that has been used at TPQ Nurul Huda Dinoyo. (2) Based on the results of the pre-test and post-test of the control and experimental groups, it was found that the experimental group using the Problem-Based Learning model had a higher score increase than the control group. The results of the Paired Sample T-Test hypothesis test showed a Sig. (2-tailed) 0.001 < 0.05, so H0 is rejected, and Ha is accepted. So, applying the Problem-Based Learning model effectively improves the reading skills of TPQ Nurul Huda Dinoyo students.